A Study of Preschool Teachers’ Perceived Stress And Their Job Satisfaction - Ling, Thong Ern (2023)
Teaching has been viewed as a stressful occupation; hence, preschool teachers are frequently reported to struggle striking a balance between work and personal life. Consequently, this will increase stress in general and decrease their job satisfaction. However, there are still limited research related to preschool teachers’ perceived stress and their job satisfaction are being discussed in local context. Hence, the present study investigates the stress and job satisfaction levels of preschool teachers in Selangor, as well as to examine the significant relationship between preschool teachers’ perceived stress and their job satisfaction in Selangor. This study applies the Herzberg’s Two-Factor Theory to investigate the correlationship between teachers’ perceived stress and their job satisfaction. Quantitative research method and correlational research design are used in this study. Two questionnaires which are Perceived Stress Scale (PSS-10) by Cohen et al. (1983) and Job Satisfaction Survey (JSS) by Spector (1988) are used. Convenient sampling is used and 73 local preschool teachers in Selangor are involved in this study. Descriptive analysis method is used to analyze the descriptive statistics included demographic profiles, mean and standard deviation of stress and job satisfaction, while Statistical Package for the Social Science (SPSS) is used to analyze the inferential statistics. The current finding’s result shows that there is a significant negative relationship between preschool teachers’ perceived stress and their job satisfaction (r = -.567, p <0.001). This study is found limited in the generalizability and sample size, and there is a tendency of centres’ rejection to involve. As recommendations, this study suggests extending the generalizability by including more regions and respondents for analysis and scheduling a better data collection period to improve participation willingness.